Factors Associated with Irritant Conjunctivitis Welding Section Workers at PT. IKI (PERSERO) - Siti Nurhalizah; Nasruddin Syam; Ulfa Sulaeman (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Industrial welding is a workplace with a high risk of causing health problems and work fatigue. Welding smoke contains dust and gas; this content can later cause several disorders, such as conjunctivitis. This study aims to determine the factors associated with irritant conjunctivitis in welding workers at PT. Indonesian Ship Industry (Persero) Makassar City. This type of research is quantitative with a cross-sectional study design. Data were analyzed using the Chi-Square statistical test. The population in this study were welding workers at PT. Indonesian Ship Industry (Persero) Makassar City. The research sample is all welding workers at PT—Indonesian Ship Industry (Persero) Makassar City, totalling 40 workers taken using the total sampling method. The results showed that there was a significant relationship between exposure to welding fumes (p=0.000), use of PPE (p=0.025) and irritant conjunctivitis and no significant relationship between knowledge (p=0.509) and irritant conjunctivitis. This study concludes that a relationship exists between exposure to welding fumes, use of PPE and irritant conjunctivitis in welding workers at PT. Indonesian Ship Industry (Persero) Makassar City.